LEGAL PERSONALITY IN THE MIDDLE OF THE EUROPEAN LEGAL REALITY - Братасюк, Віктор Миколайович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
In the article the problem of formation of legal personality in the era of the European Middle Ages. The factors that influenced this process, highlighted the uneven formation of legal personality in the different regions of the European continent.